Kelayakan Usahatani dan Strategi Pengembangan Pala Banda di Pulau Damer - Rosdianawati Woriwun; Leonard O. Kakisina; Natelda R. Timisela (Hasanuddin University, 2021)
Nutmeg (Myristica fragrans Houtt) is known as a spice plant that has high economic value and is a multipurpose plant because every part of it can be utilized. This research was carried out in March 2021 until it was completed. On Damer Island (Kehli Village and Wulur Village, Damer District). Data were collected through interviews, observations and literature studies. Sampling was carried out intentionally (purposive sampling) based on the provisions of the large population of farmers who cultivate banda nutmeg plants. Based on the Sovin formula for the population and an error rate of 15%, it can be obtained a sample of 40 nutmeg banda farmers in Wulur Village and 32 banda nutmeg farmers in Kehli Village, Damer District. This study aims to determine the income, feasibility of farming and development strategies for nutmeg on Damer Island. The results showed that the nutmeg banda farming on Damer Island was profitable so it was feasible to be developed. The results of the SWOT and QSPM analysis show that the prioritized strategy for Banda nutmeg development efforts is to improve the quality of human resources for nutmeg farmers and PPL officers. It is important that this priority strategy is carried out with pest and plant disease control programs through identification, supervision and control of plant pests and diseases, training on pest and plant disease management for farmers and PPL officers.